Studying the Level of Awareness among Malaysian Higher Educational Institutions (IPT) Regarding the Importance of Financial Counseling Through Counseling and Credit Management Agency (AKPK) from The Perspective of Maqasid Syariah - Mohd Zuki, Mohd Izzat; Mohamed Fisol, Wan Nazjmi (International Journal of Academic Research in Progressive Education and Development, 2023)
Financial counselling knowledge in the Malaysian public is crucial in helping individuals to manage and plan their finances better and more efficiently, in which financial counselling means a process in helping relationships with the choices and beliefs required in involving finances. Problems arise due to the increase in cases of insolvencies and bankruptcy among Malaysians stemming from a lack of awareness and knowledge in financial counselling, as well as the failure of the public to plan their financial management. This study aims to identify the relationship between understanding, perception, consumers’ demographic factors, and other factors with the awareness of the importance of financial counselling from the perspective of Maqasid Syariah. The type of methodology used in this study is quantitative by selecting a hundred respondents from (UniSHAMS) to answer a survey that has been prepared online and responses that have been given are analyzed to obtain data by using the Statistical Package for the Social Sciences (SPSS) to obtain descriptive and inferential values and multiple regression analysis. The findings from the analysis show that understanding factors and demographic factors are not the cause of the lack of awareness of financial counselling among members of higher learning institutions from the perspective of Maqasid Syariah. However, the perception factor strongly influences this study. The researcher hopes that with this study, the financial planning agency namely the Credit Counselling and Debt Management Agency (CCDM), also known as Agensi Kaunseling dan Pengurusan Kredit (AKPK) can increase the efforts in implementing various forms of programs in providing exposure of the importance of knowledge related to financial counselling to society, especially those from higher learning institutions. This can be done by encouraging them to get involved in the programs provided and also to improve the educational modules related to financial counselling from the perspective of Maqasid Syariah to foster awareness among the public as early as primary school.